Expanding Wilson’s information behaviour model using social cognitive theory: A case study - Peymon Montazeri (Information Research: An International Electronic Journal)
Introduction. The purpose of this paper is to expand Wilson’s information behaviour model using social cognitive theory and demonstrate its use in understanding information seeking and sharing of doctoral peers in unstructured environments.